Racial Bias and LSI-R Assessments in Probation Sentencing and Outcomes - Lowder, Evan Marie (Criminal justice and behavior, 2019)
Risk assessments are now implemented in correctional settings across the United States as an evidence-based strategy to inform sentencing and supervision decisions. Despite growing research examining racial bias in the predictive validity of risk assessments, few studies have investigated racial bias in the context of judicial decision-making. We investigated the interactive contributions of race and Level of Service Inventory-Revised (LSI-R) risk assessments in predicting sentence length and probation outcomes in 11,792 Black and White probationers. Results showed White probationers at low-risk levels received longer sentences relative to Black probationers classified at the same risk levels. However, there were few differences at higher risk levels and no evidence of racial bias in the predictive accuracy of LSI-R assessments for other probation outcomes. Findings highlight the need for prospective and carefully controlled investigations into whether risk assessments improve the fairness and accuracy of sentencing and other risk management decisions.